Crosslinking behavior of polyarylene ether nitrile terminated with phthalonitrile (PEN‐t‐Ph)/1, 3, 5‐Tri‐(3, 4‐dicyanophenoxy) benzene (TPh) system and its enhanced thermal stability. Issue 2 (25th April 2013) - Tong, Lifen; Pu, Zejun; Huang, Xu; Chen, Zhiran; Yang, Xulin; Liu, Xiaobo
ABSTRACT A novel polyarylene ether nitrile terminated with phthalonitrile (PEN‐t‐Ph) was synthesized by a simple solution polycondensation of biphenyl and hydroquinone with 2, 6‐dichlorobenzonitrile, followed by termination with 4‐nitrophthalonitrile. The PEN‐t‐Ph/1, 3, 5‐Tri‐(3, 4‐dicyanophenoxy) benzene (TPh) system was prepared by cure treatment. The phthalonitrile on PEN‐t‐Ph were thermally crosslinked with TPh in the presence of diamino diphenyl sulfone through cure treatment up to 280–340°C, which led to the transformation from thermoplastic polymers to thermosetting polymers. This is because the phthalonitrile on the PEN‐t‐Ph can react with TPh by forming phthalocyanine ring. The glass transition temperatures of the PEN‐t‐Ph/TPh system increased from 152.4°C to 194.7°C, and the initial decomposition temperature (ranging from 475.3°C to 544.0°C) increased by 68°C after thermal curing. Therefore, their thermal properties can be greatly enhanced by crosslinking. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1363‐1368, 2013